The Features of the use of Verb Part of Speech in the Northern Dialect of the Karakalpak Language - Kurbanbaeva Bazargul Reymbaevna (International Journal on Economics, Finance and Sustainable Development, 2021)
Dialectisms in the Karakalpak language are one of the least studied issues. Their study is not only for the branch of dialectology, but also for other branches of language, such as language history, ethnography, etc. In this article, prepared on the study of the northern dialect of the Karakalpak language, we talked about the peculiarities of the use of the verb in the dialect. A verb is a part of speech with compound character, with a very wide field of word formation. In the northern dialect of the Karakalpak language, the formation of the verb by the affixation method is a productive phenomenon. We divided them into two groups: noun based derivative verbs and verb based derivative verbs. Also, in the formation of the verb by word formation method, the compound verbs were studied by dividing into noun based compound verbs and verb based compound verbs. Differences in the dialect are manifested in the category of the mood of the verb in the imperative mood, the indicative mood, the conditional mood. Non-finite forms of the verb are used with dialectal differences of infinitive, gerund, and participle. In the dialect, verbs are also found in the phonetic variant. These differences are reflected in the use of vowels and consonants. In this article, we also discuss the use of dialectisms in the lexical version, the phenomenon of Elysium, the cases of abbreviated use of some syllables of words in oral speech and the usage of verbs in the portable meaning are analyzed through the facts collected from the live spoken language of the people.